(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The purpose of this study was to determine the apparatus competence in administrative structuring in Wawali Pasan Village, Ratahan District, Southeast Minahasa Regency. Based on the results of research that has been done by the author, it can be concluded as follows: Self Contept or attitude, values and self-image possessed by someone is very good. So that in resolving problems and complaints from the community the employees can do it well and without obstacles. This is because there is a good relationship that exists in the work environment or in the community Knowledge or information / knowledge possessed by village employees in the field of structuring and implementing village administration. In this case, village officials’ understanding of the demands and needs of the community regarding village administration structuring is also already good, especially for the process of structuring village administration itself. The standard operational procedures are well understood where the process starts with community data collection carried out by the respective ward head and then forwarded to the kelurahan office through the kelurahan secretary who is then submitted to the lurah head to obtain authorization and returned to the community according to their individual needs. Skills or the ability to carry out certain physical tasks (certain mental tasks) are also good enough. This is also justified by the community who believes that village officials have carried out their duties well. Although related to the efficiency of the completion of tasks and complaints from the community is still lacking. But some more understand because they know that each task and job and complaints from the community are diverse and have a difficulty level in solving it because it takes more time to solve this. Kata Kunci: Keywords: Apparatus Competence, Administrative Arrangement